Schwann Cell Precursors; Multipotent Glial Cells in Embryonic Nerves - Jessen, Kristjan R.; Mirsky, Rhona (Frontiers in Molecular Neuroscience, 2019)
The cells of the neural crest, often referred to as neural crest stem cells, give rise to a number of sub-lineages, one of which is Schwann cells, the glial cells of peripheral nerves. Crest cells transform to adult Schwann cells through the generation of two well defined intermediate stages, the Schwann cell precursors (SCP) in early embryonic nerves, and immature Schwann cells (iSch) in late embryonic and perinatal nerves. Schwann cell precursors are formed when neural crest cells enter nascent nerves and form intimate relationships with axons, a diagnostic feature of glial cells. This involves large-scale changes in gene expression, including the activation of established glial cell markers. Like early glia in the CNS, radial glia, Schwann cell precursors retain developmental multipotency and contribute to other crest-derived lineages during embryonic development. Schwann cell precursors, closely related cells termed boundary cap cells, or later stages of the Schwann cell lineage have all been implicated as the tumour initiating cell in NF1 associated neurofibromas. Immature Schwann cells are formed from Schwann cell precursors in a process that involves the appearance of additional differentiation markers, autocrine survival circuits, cellular elongation, formation of endoneurial connective tissue and basal lamina. Finally, in peri-and post-natal nerves, immature Schwann cells are reversibly induced by axon-associated signals to form the myelin and non-myelin Schwann cells of adult nerves. This article discusses these events in detail, and describes the large number of molecular signalling systems that control glial development in embryonic nerves.